The Wind in the willows - Miles, Ellen (Singapore : Scholastic Singapore, 2002)
The escapades of four animal friends who live along a river in the English countryside--Toad, Mole, Rat, and Badger.
Keywords: Children's fiction; Animals -- Fiction